(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: The objective of this study was to find the association of disease duration & patient activity loss with the incident depressive symptoms in adult orthopedic trauma patients in population of DIKhan division, Pakistan. Methods: This observational study was conducted in the department of Orthopedics Gomal Medical College DIKhan from January 01, 2020 to December 31, 2021. Patients were free of depression symptoms at the baseline & were assessed prospectively over a period of 2 years, first at 12 months of orthopedics trauma & then at 2 years for depression symptoms. Patients for depressive symptoms were assessed by Public Health Questionnaire (PHQ)-2 & PHQ-9 screening. The intensity of physical activity was assessed using METs (metabolic equivalent of task) scale. Pearson’s Chi-square test was used to find the association of dependent variable i.e. depression with independent variables i.e. Disease duration & Patient’s activity loss. The study’s end point was new-onset depression symptoms. Results: Total 630 patients were included in our study, in whom depression was found in 51 (8.0%), male 34(5.39%) and female 17(2.61%). The mean age was 42.37+/- 5.4. Among 51 patients, 38(6.03%) had duration of illness more than one year and 29(4.6%) patients with loss of activity & the results were statistically significant (p-value<0.05). Conclusion: This prospective observational study demonstrates that the patients presenting to orthopedics trauma should be screened for depressive symptoms & necessary referrals to behavioral health & psychiatric units should be made.